Produção de inferências e avaliação da compreensão leitora - Rennó, Sandra Dias da Silva (2008)
The dissertation herein inserts in the research line of Portuguese Language Reading, Writing and Teaching and is aimed to produce inferences and assessments of the reader comprehension. Knowing that all reading implies the construction of senses, we highlight that the inference is part of this process, understood as the activity to produce new information from the given information, within certain contexts (cf.: Marcuschi, 1999; Dell'Isola, 2001; Koch, 1993). To fulfill this work, we based on studies about texts and readings placed in the Textual Linguistic field and fulfilled by authors such as Beaugrande (1997), van Dijk (2004), Koch (2003a, 2003b, 2004, 2005), Marcuschi (1999) and Kleiman (2004), as well as on studies about inferences, fulfilled by Marcuschi (1999; 2003; 2005; 2008), Dell Isola (2001), and Koch (1993). Taking the purpose of control inferences produced in the reading process into consideration, we selected a text and asked students from the 6th grade in an Elementary Public School from the city of São Paulo to express in writing their comprehension on the text they read. In our check, we evidenced that students produce several inferences from the textual and knowledge tracks they have about worlds matters, their practices and experiences, reason why we can discuss, not about a single reading or sense, yet a multiplicity of readings and senses. Results still point out the need of teachers to take into consideration, while assessing the reading comprehension, the inferences the students produce, understanding that process as inseparable from the reading activity and justified, not only by the text signals, but also by the knowledge about the reader s world